STUDY ON BIOETHANOL PRODUCTION USING RED SEAWEED Eucheuma cottonii FROM BONTANG SEA WATER - Krishna Purnawan Candra; Sarwono .; Sarinah . (JOURNAL OF COASTAL DEVELOPMENT, 2011)
The increasing of energy demand for public transport and a rise of oil prices lead to intense of using green fuel for sustainable future. Red-seaweed polysaccharide consists of carrageenan can be used for production of bio-etahanol, as it supplies monosacharides. In this study, the possibility of bioethanol production using red-seaweed as raw material was examined. The purpose of this research was to determine the method of bioethanol production using red-seaweed. Two separate anaerobic fermentation following acid hydrolysis, each by different type of yeast, bread yeast (Saccharomyces cereviceae) and tapai yeast were conducted in this study. Acid hydrolysis for 2 h using H2SO4 of 5% at 100 oC of 100 g seaweed gel derived from 25 g of red-seaweed showed an optimal hydrolysis process yielded sugar content of 15.8 mg mL-1. Tapai yeast was not suitable for fermentation of red-seaweed hydrolysate, while Saccharomyces cereviceae gave an alcohol content of fermentate of 4.6% after 5-6 days of fermentation at room temperature.